Lift Enhancement of Tiltrotor Wing Using a Gurney Flap - Hao Chen; Bo Chen (International Journal of Aerospace Engineering)
A numerical investigation was undertaken to explore the lift-enhancing characteristics of the Gurney flap on a tiltrotor wing. The heights of Gurney flaps range from 1 to 4% wing chord lengths. The Navier-Stokes equations with the Spalart-Allmaras turbulence model were solved to simulate the flow structure around the Gurney flap. The computational results show that the presence of the Gurney flap can dramatically improve the tiltrotor wing lift coefficient. Compared with the baseline configuration, the maximum lift coefficient is increased by 10.67, 15.33, and 20.67% for the 1, 2, and 4% height Gurney flaps. On the other hand, the Gurney flap also results in a drag penalty, and the overall effect on the wing lift-to-drag is detrimental. In particular, at an angle of attack of 2°, use of a 4% chord length Gurney flap decreases the lift-to-drag ratio by 31.47%. Further studies demonstrate that the wing lift increments are proportional to the square root of the Gurney flap height.